The Interinstitutional Agreements in the Peruvian Practice of International Law - Mezarina García, Silvio Jesús (2019)
In the Peruvian practice of international law, the universe of international agreements is not reduced merely to treaties. In that context, this article seeks to examine the international instrument par excellence that is celebrated between public entities of at least two States. Such accord, within the framework of Peruvian legislation, is called «interinstitutional agreement».First, this paper will study the main characteristics of this kind of agreement with the purpose of identifying its legal nature. Subsequently, it will examine some of the main challenges the use of an interinstitutional agreement faces: (1) the difficulty of classifying an interinstitutional agreement as a legal norm within the Peruvian system of law sources; (2) the possible confusion with other international instruments, such as twinning arrangements (a kind of interinstitutional agreement), memoranda of understanding or collaboration agreements; (3) the possible consequences than an interinstitutional agreement infers in regard to the commission of an international illicit act in the sphere of the international responsibility of the State.